KUALITAS PELAYANAN PAJAK KENDARAAN BERMOTOR DI KANTOR SAMSAT PALABUHANRATU KABUPATEN SUKABUMI - Asep Wianto (Mimbar Administrasi Mandiri, 2022)
This study uses a qualitative approach. The informants of this study were the Head of Subdivision of TU SAMSAT Palabuhanratu, Chief of PKB Officer of SAMSAT Palabuhanratu, General Administration Staff of SAMSAT Palabuhanratu, and PKB Taxpayers. The results of the study include (1) tangible aspects in the service of receipt of Motor Vehicle Tax (PKB) payments at the Palabuhanratu SAMSAT Office is quite good (2) reliability aspects in the service of receipt of Motor Vehicle Tax (PKB) payments at the Palabuhanratu SAMSAT Office quite good, (3) the aspect of responsiveness (response/response) in the service of receipt of payment of Motor Vehicle Tax (PKB) at the Palabuhanratu SAMSAT Office is quite good and (4) the aspect of assurance (guarantee) in the service of receipt of payment of Motor Vehicle Tax (PKB) at the Office SAMSAT Palabuhanratu is quite good. Based on the results of the study, to further improve the quality of service for receipt of Motor Vehicle Tax (PKB) payments at the Palabuhanratu SAMSAT Office, it is recommended: (1). The government must pay special attention to motor vehicle tax services, (2) Efforts to increase awareness and compliance of taxpayers, (3) the public is starting to realize and take advantage of the development of information and communication technology in tax payments, (4) SAMSAT Palabuhanratu management conducts socialization in innovation payment of online PKB tax services, and (5) the Palabuhanratu SAMSAT Office must repair and complete the facilities and infrastructure for tax payment services.